Bioconversion and effect of metabolic inhibitors on secondary metabolites production during alcoholic fermentation [Bioconversión y efecto de inhibidores metabólicos sobre la producción de metabolitos secundarios durante la fermentación alcohólica] - Vejarano, Ricardo (2019)
ABSTRACT The aim of this study was to evaluate the bioconversion of metabolic inhibitors (furfural, o-vanillin, transcinnamic acid and copper) during alcoholic fermentation by Saccharomyces cerevisiae, and its effect on secondary metabolites production. The tested yeast shows a good activity to convert furfural and o-vanillin into their derivatives furfuryl alcohol and ovanillyl alcohol, respectively, both detected in the respective mediums at final of fermentative process. Also, the production of higher alcohols was affected in the presence of o-vainillin and trans-cinnamic acid, and to a lesser extent of copper, with a marked effect obtained by discriminant analysis.